KH. Hasyim Asy'ari's Thoughts on The Religious Character of Elementary School-Age Children - Ririn R. Mandar; Asril R. Mahmud; Nurjannah (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The development of science and technology today has not only had a positive impact on the development of children's character, but there are also negative impacts shown by deviant behavior that can be found in everyday life. It is suspected that one of the causes is due to the lack of strengthening the religious character of children from an early age. Therefore, the importance of strengthening religious character is instilled in students, especially elementary school-age children. KH hasyim asy'ari is one of the figures who is active and has great attention in the world of Islamic education. In the implementation of education, it prioritizes character building. From various research results, it shows that KH Hasyim Asy'ari's thoughts on religious character that must be possessed by elementary school children are purifying the heart, improving intentions, behaving qana'ah, being wara', and behaving patiently. And efforts to instill religious character values, strategies and methods are needed to support the implementation of character education for elementary school children, namely exemplary, teaching students with love and compassion, motivating students, stopping bad behavior by students, being gentle and being tawaduh (humble). These religious characters should be applied to the world of education, especially at the elementary school level.